Synergic Effect of Metal and Fluorine Doping on the Structural and Electrical Properties of La5.4MoO11.1-Based Materials. - López Vergara, Adrián; Bergillos-Ruíz, Marta; Zamudio-García, Javier; Porras-Vázquez, José Manuel; Canales-Vázquez, J.; Marrero-López, David; Ramírez-Losilla, Enrique (American Chemical Society, 2020)
Cationic and anionic frameworks of La5.4MoO11.1 proton conductors have been modified by means of metal (Ti4+, Zr4+, and Nb5+) and fluorine (F−) doping. This synergic effect leads to the stabilization of highsymmetry and single-phase polymorphs. The materials have been fully characterized by structural techniques, such as X-ray and neutron powder diffraction and transmission electron microscopy. The fluorine content was determined by ion chromatography. Impedance spectroscopy analysis under different atmospheres (dry and wet N2 and O2 and wet 5% H2−Ar) showed an improvement in the electronic conductivity under reducing conditions, making these materials potential candidates for hydrogen separation membranes.
Keywords: Separación por membrana; Química organometálica; Hydrogen separation membrane; Lanthanum molybdate